Chromium aryl complexes with N-Donor ligands as catalyst precursors for selective ethylene trimerization - Ronellenfitsch, Mathias; Wadepohl, Hubert; Enders, Markus (Organometallics, 2014)
A series of 8-amino-2-arylquinoline ligands (1-6) were synthesized and reacted with CH3CrCl2(thf)3. Under these conditions a CH bond of the 2-aryl substituent is metalated, leading to organochromium complexes with monoanionic tridentate ligands (8-13). The presence of a chromium-carbon σ bond in these complexes has been established by X-ray analysis. Furthermore, 8-(piperidin-1-yl)quinoline (14) was used as neutral bidentate ligand in addition to an external aryl group, leading to complex 15. Finally, the tris-aryl complex 18 was synthesized, which features a rare five-coordinate chromium(III) metal center. All chromium complexes were tested as catalysts for the selective trimerization of ethylene after activation with methylaluminoxane (MAO). Several of the new catalyst precursors show good behavior for the selective trimerization of ethylene. Although chlorido ligands in the catalyst precursor will be substituted by methyl groups during the activation with MAO, there is a clear difference in the catalytic behavior when the complex contains a methyl (or aryl) group prior to addition of MAO. The mechanism of catalyst activation has been studied in more detail with the tris-aryl complex 18.